1999
DOI: 10.1159/000018117
|View full text |Cite
|
Sign up to set email alerts
|

Split-Face Clinical and Bio-Instrumental Comparison of 0.1% Adapalene and 0.05% Tretinoin in Facial Acne

Abstract: Background: Adapalene and tretinoin are topical compounds active for treating acne. Objective: To compare the efficacity and safety of adapalene 0.1% gel and tretinoin 0.05% gel in moderately severe facial acne using clinical and objective biometrological assessments. Such information is currently lacking in the literature. Methods: The split-face method was used in 25 acne volunteers for a 6-week treatment. In addition to clinical counts of lesions, the amount of comedones was assessed using computer-assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
2
17
0
2
Order By: Relevance
“…Retin-A Ò produced a significant comedolytic effect agreeing with data from previous authors obtained for different body sites [10,11]. In addition, the study detected differences between products.…”
Section: Discussionsupporting
confidence: 91%
“…Retin-A Ò produced a significant comedolytic effect agreeing with data from previous authors obtained for different body sites [10,11]. In addition, the study detected differences between products.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, in a Adapalene 0.1% gel vs tretinoin 0.025% gel split-face clinical and bio-instrumental comparison of 0.1% adapalene and 0.05% tretinoin gel in facial acne, the erythema index 39 and squamometry values were used to quantitate skin irritation. 27 The evaluation of skin colour outside the acne lesion using narrowband refractive sphectrophotometry showed the development of minimal erythema on both the treated sides. The between-product comparison indicated that erythema was transiently more pronounced on the tretinoin 0.05% gel treated side at weeks 2 and 4, with no further difference at week 6.…”
Section: Clinical Evaluationmentioning
confidence: 98%
“…In contrast to previous studies, the present trial revealed the greater efficacy of tretinoin 0.05% gel over adapalene 0.1% gel. This may be ascribed to the higher concentration of tretinoin, 27 and its higher affinity for gamma receptors. 33 The adverse reactions to adapalene are of the same type, but of significantly lower frequency and lesser severity than for tretinoin (Table IV).…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The material is stained with toluidine blue and basic fuchsin dyes for 3 min. This method combined with computerized image analysis [24, 25, 26, 27]allows to quantify the density and size of follicular casts and comedones (fig. 5).…”
Section: Cyanoacrylate Skin Surface Strippingsmentioning
confidence: 99%